Analisis Konsep Fisika Pada Alat Musik Rebana - Singgih Bektiarso; I Ketut Mahardika; Mohamad Fikri; Izzha Mayzy Az-zahra Putri; Umi Fatimah; Sayyidatun Najah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Musical instruments in Indonesia are very diverse, one of which is the tambourine. The tambourine is a round musical instrument made of wood and cowhide. The tambourine instrument is often played in several events such as commemorations of Islamic holidays, weddings, festivities, and so on. But behind this game of the tambourine, there is a physics concept that causes the tambourine to make a beautiful sound. This study uses a qualitative descriptive analysis method with an emphasis on observing the tambourine while it is being played and interviews with one of the players of the tambourine. From this analysis, several physics concepts contained in the game of the tambourine musical instrument will be produced.